CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA BANK TERDAFTAR DI BURSA EFEK INDONESIA - Nilhasanah, Nilhasanah (UNIB Press, 2018)
The purpose of this study is to examine the relationship between corporate social performance and financial performance. In addition, this study also aims to examine corporate social responsibility disclosure as a moderating variable the relationship between corporate social performance and financial performance of banking companies in Indonesia. The sample consisted of 35 listed bank in Indonesia Stock Exchange. The results of the study showed that the corporate social responsibility performance negatively effect financial performance. This means that the higher the cost of corporate social responsibility, the lower the company's financial performance. In testing the effect of moderating variable, the results of this study does not provide evidence that the corporate social responsibility disclosure as a moderating variable relationship between corporate social performance and financial performance. However, other results in this study showed that as the independent variable, the corporate social responsibility disclosure positively effect on financial performance, which means that the more items that disclosed the company, the higher the company's financial performance.